Circumferential suture of the breast with the Brito-Moscozo needle: an alternative suture technique for the breast pillars during mammoplasty - Francisco Anibal Passos de Brito; Marcus Vinicius Alfano Moscozo (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Mammoplasty is one of the most common plastic surgeries in the world. Several techniques have been described for breast volume reduction and mastopexy. For maintaining the conical shape of the breast, breast pillars have been traditionally fixed with sutures from the center of the breast by using commercially available standardized needles. This paper reports an alternative suture technique that uses a Brito-Moscozo needle to create circumferential sutures around the breast pillars during mammoplasty. METHODS: We describe a circumferential suture technique for the breast pillars and the material used. RESULTS: From December 2013 to January 2015, 22 cases of reduction mammoplasty and mastopexy were performed with circumferential sutures around the breast pillars. No complications related to the technique were observed. CONCLUSION: This study verified the applicability of our circumferential suture technique that used a Brito-Moscozo needle to fix the breast pillars. In all the patients who underwent the procedure as an alternative to conventional suture in the center of the breast, fewer sutures and shorter surgical time were required.